Parastomal gallbladder herniation: A case report and review of the literature. (2020) - Moeckli, Beat; Limani, Perparim; Clavien, Pierre-Alain; Vonlanthen, Rene
Highlights: Gallbladder herniation is a rare complication of a parastomal hernia, affecting primarily elderly females. For patients with parastomal swelling and pain gallbladder herniation should be included in the differential diagnosis. Elderly patients with multiple comorbidities may benefit from a conservative approach instead of surgery. The use of prophylactic mesh when creating a permanent end colostomy reduces the rate of parastomal hernias. Abstract: Introduction: Parastomal hernia is a common complication of patients living with an enterostomy. However, a parastomal hernia involving the gallbladder is a rare condition with only eight cases documented in the literature. Presentation of case: We report the case of a 69-year old female who underwent an open right hemicolectomy with creation of a colostomy and terminal ileostomy. She presented with parastomal swelling and pain 16 months later. A computed tomography scan revealed a parastomal herniation of the gallbladder. We elected to proceed with a cholecystectomy and hernia repair, the patient was asymptomatic at her last follow-up. Discussion: A systematic search of the literature found eight previously published cases. This condition primarily affects elderly females. Five patients were treated surgically and three conservatively, all with a favorable outcome. In frail patients without complicating factors, a conservative treatment approach with surveillance may be safe. We chose a surgical approach due to the symptomatic nature of the presentation and the gallstone containing hernia. This is the first case of a parastomal gallbladder herniation containing a large gallstone. Conclusion: This report should help broadening the physician's differential diagnosis in dealing with patients with symptomatic parastomal hernias and provide an example for diagnosis and management of this complication.